The contribution of inhibitory interneurons to circuit dysfunction in Fragile X Syndrome - Cea-Del Rio, Christian A.; Huntsman, Molly M. (Frontiers in Cellular Neuroscience, 2014)
Many neurological disorders, including neurodevelopmental disorders, report hypersynchrony of neuronal networks. These alterations in neuronal synchronization suggest a link to the function of inhibitory interneurons. In Fragile X Syndrome (FXS), it has been reported that altered synchronization may underlie hyperexcitability, cognitive dysfunction and provide a link to the increased incidence of epileptic seizures. Therefore, understanding the roles of inhibitory interneurons and how they control neuronal networks is of great importance in studying neurodevelopmental disorders such as FXS. Here, we present a review of how interneuron populations and inhibition are important contributors to the loss of excitatory/inhibitory balance seen in hypersynchronous and hyperexcitable networks from neurodevelopmental disorders, and specifically in FXS.